Pengaruh Temperatur Tempering Terhadap Kekerasan dan Ketangguhan pada Baja Karbon Sedang St60 - Bimas Saputra, Ebit (Jurnal Greenation Ilmu Teknik, 2023)
This study aims to determine the effect of tempering temperature on the hardness and toughness of ST60 medium carbon steel. Beginning with the hardening process aimed at increasing the natural hardness of the steel, then tempering, aimed at reducing residual stress, hardness, so that it is ductile and has toughness. The method used is an experimental approach. The object of research is hardness and toughness test specimens. Each consists of five groups; I control, II hardening, III tempering 1500C, IV tempering 3500C, and V tempering 5500C. The results of the hardness study showed an increase in hardness in the specimens of group II which had a higher hardness of 445.33 HB, group III had a hardness of 436.83 HB and IV had a hardness of 393.75 HB, while in group V there was a decrease in hardness, which had a hardness 326.41 Hb. Compared to group I which has a hardness of 380.83 HB. While the results of the toughness study showed a decrease in energy absorption in group II, namely 29.596 NM and group III, namely 33.2416 NM, while an increase in energy absorption in group IV, namely 80.8421 NM and group V 163.598 NM, compared to group I, which had an energy absorption of 50 .35N.M.